(3ebOeI aj Yde GdEOGQIs - (3HQfGQO(B, (3JGjdhQ GdKGdKs ((3GdQjGV(B:s (3OGQ GdeQjN,s, 2007)
(3jVe GdGMJeGd hGdGMUGA, JMdjd GdbQGQ, JMdjd GdUaha, GdeMGcGI, GdJfHD, EOGQI GdeNRhfs
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdEOGQIs; (3GdEOGQI(B- (3GdWQb GdEMUGFjI s